Optimization of Xylitol Production from Tobacco Stem Using Ultrasound-Assisted Acid Hydrolysis Coupled with Fermentation - Yukti Nurani; Bekti Palupi; Diana Madhuri; Diah Tri Wulandari; Ansori Ansori (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Tobacco (Nicotiana tabacum L.), as one of the main commodities in East Java Province, where only the leaves are utilized, while the stems become agricultural waste and are often burned, contributes to air pollution. Nonetheless, these tobacco stems possess potential for high-value chemical products, such as xylitol. This study investigated the optimum operating conditions for producing xylitol from tobacco stem waste. The process employed Ultrasound-Assisted Acid Hydrolysis followed by fermentation using Candida tropicalis. Hydrolysis was conducted in an ultrasonic bath that operates at 40 kHz and 50 watts, using 0.1 N H₂SO₄ as the solvent. The resulting hydrolysate was then fermented by adding Candida tropicalis (20 mL per 100 mL substrate) and incubating for 48 hours, 30 °C, 120 rpm shaker. Optimization was conducted utilizing Response Surface Methodology method to assess the interactions between operating variables (temperature, time, and volume of solvent during hydrolysis) and xylitol yield. The study investigated the optimum operating conditions to produce xylitol were 30 °C, 50 minutes, and 150 mL of solvent, yielding xylitol at a concentration of 5.6 g/L.